Perbaikan Budidaya Polikultur Lidah Buaya (Aloe vera Linn) dan Kacang Panjang (Vigna unguiculata) Menggunakan Biakan Rhizobium - Purwaningsih, Sri; Saefudin, Saefudin; Budiarjo, Budiarjo (Universitas Atma Jaya Yogyakarta, 2004)
Polyculture cultivation improvement of Aloe vera Linn (A. vera Linn) and Vigna unguiculata (V. unguiculata) has been done using Rhizobium strains inoculation onto V. unguiculata seeds to increase their growth and production. The study was done in Ciomas district, Bogor, using rice paddy field with a total of 24th plots of 1 x 2,5m2 width. A. vera Linn was planted until two months old using an interval of 60 x 60 cm2. The Rhizobium used were strains number 171, 172, 173, and their combination of those three, which was planted using an interval of 20 x 35 cm2. The negative controls were uninoculated, without N (K1) and the positive controls were uninoculated, with urea fertilizer equal to 100 kg/ha (K2). The experiment design was using Randomized Complete Block Design (RCBD) with four replications. The parameters used were leaves numbers, dry weight of plants, roots, root nodules, and pods production of V. unguiculata and leaves number, leaves length and width of A. vera. Results showed that isolate number of 172 (isolate of Glycine max Linn.) had given the best results on the production of V. unguiculata in the polyculture system with A. vera.